patient awareness at the Umbulharjo I Health Center Yogyakarta towards handling unused drugs. - Woro Supadmi, S.Si., Apt.; Faqihuddin Najib; Dwi Hastuti (Majalah Farmaseutik, 2023)
ABSTRACTUnused drugs have adverse economic, environmental and health impacts. Behavioral awareness of handling unused drugs can be influenced by the environment, information obtained and one's habits. The purpose of this study was to determine the relationship between the characteristics of respondents and patient awareness at the Umbulharjo I Health Center Yogyakarta towards handling unused drugs.The study design was observational cross sectional with data collection using questionnaires. The number of samples determined based on Lemeshow's formula was obtained 69 of purposive sampling technique. The study sample was patients who visited Puskesmas Umbulharjo 1 who met the inclusion criteria. Research instruments in the form of questionnaires on the characteristics and awareness of patients towards handling unused drugs, questionnaires have been tested for reliability and validity. Data analysis using chi-square test through SPSS v.16.0 for Windows.The results of the study based on patient characteristics were 71.0% aged 18-30 years, female 55.1%, high school education reached 50.7% and worked 69.6%. There were no significant associations between age (p = 0.491) and sex (p = 0.272) and occupation (p = 0.465) with awareness of unused drug handling. There was a significant relationship between education (p = 0.019) and awareness of handling unused drugs.The conclusion of this study is a relationship between patient education at Puskesmas Umbulharjo I and awareness of handling unused drugs.